2023
DOI: 10.29235/1561-8323-2023-67-1-59-65
|View full text |Cite
|
Sign up to set email alerts
|

Mucin expression in liver cancer

Abstract: Increasing incidence, difficulties in early diagnosis, and a high mortality rate in liver cancer (LC) determine the relevance of studying the mechanisms of its development. The aim of the work is to evaluate the expression of high molecular weight glycoproteins MUC-1, MUC-13 in liver cancer. The object of study is LC tissue samples of 65 patients from the archives and 34 blood serum samples from patients with morphologically confirmed LC. The age of subjects was 26– 97 years. The level of antibodies to MUC-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Thus a knowledge of the electrochemistry and thermodynamics of ytterbium chlorides in molten salts is crucial for the understanding of spent fuel recycling. In pyrochemical processes chlorides of lanthanides are usually diluted in molten salt medium and in our works have been shown that the electrochemical transient techniques is not only a powerful method for studying electrode kinetics, but also an effective method for the determination of thermodynamic properties (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 95%
“…Thus a knowledge of the electrochemistry and thermodynamics of ytterbium chlorides in molten salts is crucial for the understanding of spent fuel recycling. In pyrochemical processes chlorides of lanthanides are usually diluted in molten salt medium and in our works have been shown that the electrochemical transient techniques is not only a powerful method for studying electrode kinetics, but also an effective method for the determination of thermodynamic properties (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 95%
“…In pyrochemical processes chlorides of lanthanides are usually diluted in a molten salt medium and our works showed that the electrochemical transient techniques are not only a powerful tool for studying electrode kinetics, but also an effective method for the determination of thermodynamic properties. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The standard redox potentials of the Yb(III)/Yb(II) redox couple relative to the Pt(II)/Pt electrode in the LiCl-KCl melt have been measured at different temperatures. 23 Preliminary results on the diffusion coefficients (D) for Yb(III) and Yb(II) were determined by cyclic voltammetry, chronoamperometry and chronopotentiometry in KCl, CsCl, and the equimolar NaCl-KCl melts.…”
mentioning
confidence: 99%